2015
DOI: 10.1093/mnras/stv545
|View full text |Cite
|
Sign up to set email alerts
|

Ultracool white dwarfs and the age of the Galactic disc★

Abstract: We present parallax observations and a detailed model atmosphere analysis of 54 cool and ultracool (T eff < 4000 K) white dwarfs (WDs) in the solar neighbourhood. For the first time, a large number of cool and ultracool WDs have distance and tangential velocities measurements available. Our targets have distances ranging from 21 pc to > 100 pc, and include five stars within 30 pc. Contrary to expectations, all but two of them have tangential velocities smaller than 150 km s −1 thus suggesting Galactic disc mem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 59 publications
2
55
1
Order By: Relevance
“…Few intrinsically faint WDs have parallax measurements. Gianninas et al (2015) obtained parallaxes for 54 cool WDs, and all 6 of their ultracool WDs ( < T 4000 K eff ) have masses less than 0.4M ☉ , versus the typical mass for hotter WDs of~M 0.6 ☉ assumed in our analysis. A 4000K pure hydrogen atmosphere WD with a mass of 0.3M ☉ is ∼0.7 mag brighter than a 0.6M ☉ WD of the same temperature and atmospheric composition.…”
Section: Disk Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…Few intrinsically faint WDs have parallax measurements. Gianninas et al (2015) obtained parallaxes for 54 cool WDs, and all 6 of their ultracool WDs ( < T 4000 K eff ) have masses less than 0.4M ☉ , versus the typical mass for hotter WDs of~M 0.6 ☉ assumed in our analysis. A 4000K pure hydrogen atmosphere WD with a mass of 0.3M ☉ is ∼0.7 mag brighter than a 0.6M ☉ WD of the same temperature and atmospheric composition.…”
Section: Disk Resultsmentioning
confidence: 69%
“…The overall impression of Figure 23 is that it is consistent with our high adopted fraction of hydrogen atmosphere WDs past the turnover, and that clearly more accurate infrared photometry has the potential to allow unambiguous classification of atmospheric composition for stars cooler thanT 4000 K eff . Kilic et al (2010a) fraction of helium WDs we've adopted (see also Gianninas et al 2015).…”
Section: Disk Resultsmentioning
confidence: 99%
“…However, from MS and WD populations, it has been shown that oldest stars within the disk have an age of 8-10 Gyr (e.g. Oswalt et al 1996;Bergeron et al 1997;del Peloso et al 2005;Salaris 2009;Haywood et al 2013;Gianninas et al 2015).…”
Section: Star Formation Historymentioning
confidence: 99%
“…c Paper II is Kilic et al (2012). d Paper III is Gianninas et al (2015). e Paper IV is Dame et al (2016).…”
Section: Simulation Studymentioning
confidence: 99%
“…from the literature (Kilic et al 2010(Kilic et al , 2012Gianninas et al 2015;Dame et al 2016). The atmospheric compositions and priors on distance moduli for these 10 stars are listed in Table 4.…”
Section: Analysis Of a Group Of Candidate Halo White Dwarfsmentioning
confidence: 99%